Storytelling-Based Nursing Communication During Hospitalization: Its Impact On Anxiety And Influencing Factors In Preschool Children: A Systematic Review - Citra Suraya; Aris Citra Wisuda; Tukimin bin Sansuwito; Regidor III Dioso; Dian Emiliasari (Institut Citra Internasional, 2025)
Hospitalization often triggers anxiety in preschool children due to unfamiliar environments, parental separation, and invasive procedures. Storytelling-based nursing communication has shown promise as an effective intervention to reduce this anxiety. This systematic review explores the effectiveness and influencing factors of hospitalization anxiety in children aged 3–6 years. Literature was searched from PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2020 and 2025. Nine experimental or quasi-experimental studies from Indonesia, Iran, Brazil, Italy, and Turkey met the inclusion criteria, all involving nurse-led storytelling interventions. Most studies reported significant reductions in anxiety. Key influencing factors included age, length of stay, hospitalization history, parental presence, and storytelling methods. The intervention consistently enhanced emotional comfort, reduced fear, and strengthened nurse-child interaction. In conclusion, storytelling is an effective non-pharmacological strategy to reduce hospitalization anxiety in preschool children and supports child-centered nursing care when tailored to the child’s developmental stage, experiences, parental involvement, and cultural context.